Design, synthesis, and molecular docking studies of thiazolidinediones as PPAR‐γ agonists and thymidylate synthase inhibitors. Issue 9 (14th May 2021) - Nazreen, Syed
Abstract: New thiazolidine‐2, 4‐dione hybrids were designed and synthesized as potential peroxisome proliferator‐activated receptor (PPAR)‐γ agonists and thymidylate synthase inhibitors. All the synthesized compounds follow Lipinski's and Veber's rules and possess the desired pharmacokinetics properties. The PPAR‐γ transactivation results displayed that compounds 12 (78.9%) and 11 (73.4%) were the most active compounds and they increased PPAR‐γ gene expression by 2.2‐ and 2.4‐fold, respectively. Compounds 12, 11, and 8 showed promising cytotoxicity, with IC50 values ranging from 1.4 to 4.5 μM against MCF‐7 cells and from 1.8 to 8.4 μM against HCT‐116 cells. Compounds 11 and 12 also inhibited thymidylate synthase with IC50 values of 5.1 and 3.2 μM, respectively, confirming their mode of action as thymidylate synthase inhibitors. Finally, molecular docking studies supported the in vitro biological activity results. Abstract : New thiazolidine‐2, 4‐dione hybrids were designed and synthesized as potential peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) agonists and thymidylate synthase (TS) inhibitors. Compounds 12 and 11 as the most active compounds increased PPAR‐γ gene expression by 2.2‐ and 2.4‐fold, respectively. Compounds 12, 11, and 8 showed promising cytotoxicity against MCF‐7 and HCT‐116 cells. Compounds 11 and 12 were also confirmed as TS inhibitors. ​